IMPLEMENTASI FUNGSI MEDIASI DALAM PENYELESAIAN SENGKETA HARTA WARISAN DI PENGADILAN AGAMA KOTA MEDAN (Studi Terhadap Perma No. 1 Tahun 2016 Tentang Prosedur Mediasi di Pengadilan) - Pagar, Hafsah, Ahmad Muhajir Nasution, (AT-TAFAHUM: Journal of Islamic Law, 2018)
Abstract The focus of this research is still the high number of inheritance disputes in the Medan city religious court, moreover coupled with the number of parties to the inheritance dispute not reached the peace path ordered by the panel of judges, so that the effectiveness and efficiency aspired by the supreme court regulation no. 1 of 2016 is less than optimal in the Medan city religious court. Of course this requires follow-up in solving these problems, so that later it is expected that a solution will be obtained to correct the problems mentioned above in order to achieve effectiveness and efficiency as mandated by the Supreme Court regulation no. 1 year 2016. In Article 21 of the Supreme Court Regulation No. 1 of 2016 concerning Mediation Procedures in the Court, stated that: (1) the mediator determines the day and date of the mediation meeting, after receiving the appointment as mediator. (2) in the case of mediation carried out in a court building, the mediator on the basis of the power of a case examiner through the court clerk calls the parties with the help of a substitute bailiff to attend a mediation meeting. (3) the power referred to in paragraph (2) is for the sake of law without the need to make a power of attorney, so that without a separate instrument from the case check judge, the bailiff or substitute bailiff must carry out the order of the judge and non-judge mediator to call.